Abundant Chitinous Structures in Chilostomella (Foraminifera, Rhizaria) and Their Potential Functions. (20th November 2020) - Nomaki, Hidetaka; Chen, Chong; Oda, Kaya; Tsuchiya, Masashi; Tame, Akihiro; Uematsu, Katsuyuki; Isobe, Noriyuki
Abstract: Benthic foraminifera, members of Rhizaria, inhabit a broad range of marine environments and are particularly common in hypoxic sediments. The biology of benthic foraminifera is key to understanding benthic ecosystems and relevant biogeochemical cycles, especially in hypoxic environments. Chilostomella is a foraminiferal genus commonly found in hypoxic deep‐sea sediments and has poorly understood ecological characteristics. For example, the carbon isotopic compositions of their lipids are substantially different from other co‐occurring genera, probably reflecting unique features of its metabolism. Here, we investigated the cytoplasmic and ultrastructural features of Chilostomella ovoidea from bathyal sediments of Sagami Bay, Japan, based on serial semi‐thin sections examined using an optical microscope followed by a three‐dimensional reconstruction, combined with TEM observations of ultra‐thin sections. Observations by TEM revealed the presence of abundant electron‐dense structures dividing the cytoplasm. Based on histochemical staining, these structures are shown to be composed of chitin. Our 3D reconstruction revealed chitinous structures in the final seven chambers. These exhibited a plate‐like morphology in the final chambers but became rolled up in earlier chambers (toward the proloculus). These chitinous, plate‐like structures may function to partition the cytoplasm in a chamber to increase the surface/volume ratio and/or act as a reactive site for some metabolic functions.